PELAKSANAAN PEMBIAYAAN MURABAHAH SEKTOR MIKRO PADA PT. BANK BRI SYARIAH CABANG PADANG - Nurhikmah Nurhikmah (IAIN Batusangkar, 2015)
: In this qualitative study, the researcher analyzed the implementation of micro sector of murabahah financing in PT Bank BRI Syariah Padang Branch. The findings revealed that the information which was received by the customer uncompleted, the customer did not understand the content of murabahah. The negotiation both customer and the bank were not done well. Every transaction, the bank gave the highest margin and the margin was determined by the bank. This concept was not related to the principle of An-Tarradin Minkum. Kata Kunci: Micro Sector, Murabahah, Bank Syariah